Report on Candidates' Work in the Secondary Education Certificate General and Basic Proficiency Examinations June 1992: Technical Drawing - Caribbean Examinations Council (CXC, 1992)
This report contains general and detailed comments on the performance of candidates in the June 1992 Caribbean Secondary Education Certificate (CSEC) general and basic proficiency examinations in Technical Drawing.
Keywords: CXC CSEC examinations